ChemInform Abstract: Diplomorphanins A and B: New C‐Methyl Flavonoids from Diplomorpha canescens. Issue 29 (1st July 2013) - Devkota, Hari Prasad; Watanabe, Masato; Watanabe, Takashi; Yahara, Shoji
Abstract: Diplomorphanins A, (I), and B, (II), are isolated from the aerial parts of D.